Single-molecule spectroscopic studies of thin-film chemical gradients - Giri, Dipak (Kansas State University, 2016)
This dissertation describes the application of single molecule spectroscopy and tracking to investigations of the nanoscale properties of thin-film chemical gradients and the transport dynamics of molecules dispersed within and upon these gradients. Chemical gradients are surface bound materials that incorporate gradually changing chemical and/or physical properties. A continuous and gradual change in the properties of gradients are expected and often required for their intended applications, which range from directed growth of cell colonies to combinatorial materials science. In reality, such conditions are almost never met due to spontaneous demixing and dewetting processes that can lead to properties variations on microscopic length scales. A better understanding on the properties of chemical gradients on microscopic length scales will aid in the production of better engineered materials. Single molecule spectroscopy (SMS) allows for gradient properties to be probed on nanometer-to-micrometer length scales. In this dissertation, quantitative measurements of gradient polarity (i.e., dielectric properties) are made along a sol-gel derived thin film that incorporates a macroscopic polarity gradient. These measurements report on the microscopic heterogeneity of the gradient film, and point to the occurrence of phase separation of the polar and nonpolar components along the gradient. Single molecule tracking (SMT) provides an important means to examine the dynamics of molecular mass transport in thin films and on surfaces. In this dissertation, SMT is employed to study mass transport in thin water films condensed over monolayer wettability gradients under ambient environments. The results show that the rate and the mechanism of molecular transport depend on the surface wettability, and on the ambient relative humidity. Finally, wettability gradients have been broadly used to drive the transport of liquid droplets. In this dissertation, these applications are extended to achieve spontaneous stretching of DNA by the propulsion of liquid droplets along the gradient. Single molecule fluorescence imaging of DNA stretched along these gradients demonstrates that hydrophobic surfaces play an important role in DNA stretching. The study also shows the surface tension force acting at the gradient-droplet contact line (interface) to be responsible for DNA elongation and alignment. Overall, single molecule methods have been shown to be highly useful for better understanding the properties of chemical gradients as described in this dissertation.
Keywords: Single molecule spectroscopy; Chemical gradients; Thin films; Self-assembled monolayers; Fluorescence; DNA stretching